Isolated Oculomotor Nerve Palsy: an unusual Presentation of Temporal Lobe Tumor - Sharma, Kumudini (Medknow Publications Pvt Ltd, 2010)
INTRODUCTION: Temporal lobe tumors commonly present with seizures, headache, auditory and visual hallucination, memory disturbance. Isolated cranial neuropathies are rare in patients with tumors affecting temporal lobe. METHODS AND MATERIAL: The authors report a retrospective review of two cases of glioblastoma multiforme of the temporal lobe presenting with isolated oculomotor nerve palsy as their clinical feature. RESULTS: Oculomotor nerve palsy in the temporal lobe tumor occurs primarily as result of herniation of uncus through the tentorium cerebellli. The tumors located anteromedially in the temporal lobe are usually asymptomatic and sudden medial expansion of these tumors due to intratumoral hemorrhage causes direct compression of the adjacent third nerve, which lies in the suprolateral border of the cavernous sinus, thereby producing painful oculomotor nerve palsy as the isolated clinical feature of these temporal lobe lesions. CONCLUSIONS: The authors conclude that the differential diagnosis of painful isolated oculomotor nerve palsy should also include tumor of temporal lobe located anteromedially with intratumoral hemorrhage, in addition to the rupture of an aneurysm of posterior communicating artery.